Phytochemical Test, Toxicity and Antioxidant Activity Leaves Kerehau (Callicarpa longifolia Lam.) With DPPH Method - Erwin Erwin; Redda An Nisa; Daniel Daniel (Hasanuddin University, 2015)
Phytochemical analysis, toxicity test by the brine shrimp lethality test (BSLT) against Artemia salina L, and antioxidant activity evaluation of the extracts of Kerehau leaves (Callicarpa longifolia Lam.) have been carried out. The ethanol extract obtained from Kerehau leaves was concentrated by using a rotary vacuum evaporator. Furthermore, the crude extract was fractionated with n-hexane and ethyl acetate solvent, successively. The phytochemical analysis of crude extract constitutes alkaloids, phenolics, flavonoids and steroids. n-hexane fraction contains alkaloids, flavonoids and steroids and ethyl acetate fraction contain alkaloids, phenolics and flavonoids. n-Hexane fraction exhibited highest toxic activity with LC50 value 90.05 ppm against Artemia salina L and ethyl acetate fraction has the highest antioxidant activity with IC50 value 38.94 ppm compared with other extracts.